Direct analysis in real time-mass spectrometry for rapid quantification of five anti-arrhythmic drugs in human serum: application to therapeutic drug monitoring - Yuzhou Gui (Nature Portfolio, 2020)
Abstract Therapeutic drug monitoring (TDM) is necessary for the optimal administration of anti-arrhythmic drugs in the treatment of heart arrhythmia. The present study aimed to develop and validate a direct analysis in real time tandem mass spectrometry (DART–MS/MS) method for the rapid and simultaneous determination of five anti-arrhythmic drugs (metoprolol, diltiazem, amiodarone, propafenone, and verapamil) and one metabolite (5-hydroxy(OH)-propafenone) in human serum. After the addition of isotope-labeled internal standards and protein precipitation with acetonitrile, anti-arrhythmic drugs were ionized by DART in positive mode followed by multiple reaction monitoring (MRM) detection. The use of DART–MS/MS avoided the need for chromatographic separation and allowed rapid and ultrahigh throughput analysis of anti-arrhythmic drugs in a total run time of 30 s per sample. The DART–MS/MS method yielded satisfactory linearity (R2 ≥ 0.9906), accuracy (86.1–109.9%), and precision (≤ 14.3%) with minimal effect of biological matrixes. The method was successfully applied to analyzing 30 clinical TDM samples. The relative error (RE) of the concentrations obtained by DART–MS/MS and liquid chromatography-tandem mass spectrometry (LC–MS/MS) was within ± 13%. This work highlights the potential usefulness of DART for the rapid quantitative analysis of anti-arrhythmic drugs in human serum and gives rapid feedback in the clinical TDM practices.